Crabtree Effect on Rhodosporidium toruloides Using Wood Hydrolysate as a Culture Media - Carlos S. Osorio-González; Rahul Saini; Krishnamoorthy Hegde; Satinder Kaur Brar; Alain Lefebvre; Antonio Avalos Ramírez (Fermentation, 2022)
The interest in microorganisms to produce microbial lipids at large-scale processes has increased during the last decades. Rhodosporidium toruloides-1588 could be an efficient option for its ability to simultaneously utilize five- and six-carbon sugars. Nevertheless, one of the most important characteristics that any strain needs to be considered or used at an industrial scale is its capacity to grow in substrates with high sugar concentrations. In this study, the effect of high sugar concentrations and the effect of ammonium sulfate were tested on R. toruloides-1588 and its capacity to grow and accumulate lipids using undetoxified wood hydrolysates. Batch fermentations showed a catabolic repression effect on R. toruloides-1588 growth at sugar concentrations of 120 g/L. The maximum lipid accumulation was 8.2 g/L with palmitic, stearic, oleic, linoleic, and lignoceric acids as predominant fatty acids in the produced lipids. Furthermore, R. toruloides-1588 was able to utilize up to 80% of the total xylose content. Additionally, this study is the first to report the effect of using high xylose concentrations on the growth, sugar utilization, and lipid accumulation by R. toruloides-1588.